Design, Synthesis and in vitro Evaluation of Indolotacrine Analogues as Multitarget‐Directed Ligands for the Treatment of Alzheimer's Disease. (2nd October 2015) - Benek, Ondrej; Soukup, Ondrej; Pasdiorova, Marketa; Hroch, Lukas; Sepsova, Vendula; Jost, Petr; Hrabinova, Martina; Jun, Daniel; Kuca, Kamil; Zala, Dominykas; Ramsay, Rona R.; Marco‐Contelles, José; et al.
Abstract: Novel indolotacrine analogues were designed, synthesized, and evaluated as potential drugs for the treatment of Alzheimer's disease. By using a multitarget‐directed ligand approach, compounds were designed to act simultaneously as cholinesterase (ChE) and monoamine oxidase (MAO) inhibitors. The compounds were also evaluated for antioxidant, cytotoxic, hepatotoxic, and blood–brain barrier (BBB) permeability properties. Indolotacrine9 b (9‐methoxy‐2, 3, 4, 6‐tetrahydro‐1 H ‐indolo[2, 3‐ b ]quinolin‐11‐amine) showed the most promising results in the in vitro assessment; it is a potent inhibitor of acetylcholinesterase (AChE IC50 : 1.5 μm ), butyrylcholinesterase (BChE IC50 : 2.4 μm ) and MAO A (IC50 : 0.49 μm ), and it is also a weak inhibitor of MAO B (IC50 : 53.9 μm ). Although its cytotoxic (IC50 : 5.5±0.4 μm ) and hepatotoxic (IC50 : 1.22±0.11 μm ) profiles are not as good as those of the standard 7‐methoxytacrine (IC50 : 63±4 and 11.50±0.77 μm, respectively), the overall improvement in the inhibitory activities and potential to cross the BBB make indolotacrine9 b a promising lead compound for further development and investigation. Abstract : MAO meets ChE ! By using a multitarget‐directed ligand approach, a series of novel compounds were designed to act simultaneously as cholinesterase (ChE) and monoamine oxidase (MAO) inhibitors. The most promising compound, indolotacrine9 b, was found to be a potent inhibitor of both cholinesterases and MAO A and a moderately potent inhibitor of MAO B.